We lie here [large type] - Hall, Rachel Howzell (Center Point Large Print, 2023)
"TV writer Yara Gibson's hometown of Palmdale, California, isn't her first choice for a vacation. But she's back to host her parents' twentieth-anniversary party and find the perfect family mementos for the celebration. Everything is going to plan until Yara receives a disturbing text: "I have information that will change your life." The message is from Felicia Campbell, who claims to be a childhood friend of Yara's mother. But they've been estranged for years - drama best ignored and forgotten. But Yara can't forget Felicia, who keeps texting, insisting that Yara talk to her "before it's too late." But the next day is already too late for Felicia, whose body is found floating in Lake Palmdale. Before she died, Felicia left Yara a key to a remote lakeside cabin. In the basement are files related to a mysterious tragedy, unsolved since 1998. What secrets was Felicia hiding? How much of what Yara knows about her family has been true? The deeper Yara digs for answers, the more she fears that Felicia was right. Uncovering the truth about what happened at the cabin all those years ago will change Yara's life - or end it."--